2022
DOI: 10.11591/ijere.v11i2.22112
|View full text |Cite
|
Sign up to set email alerts
|

The impact of ICT utilization to improve the learning outcome: A meta-analysis

Abstract: <span lang="EN-US">This study aimed to describe the impact of the utilization of technology on learning outcomes through a meta-analysis. Data was collected by documenting research that is resulted from various sources collected through internet. These articles were published from 2006 to 2019, in United Nations Language. The article discusses the influence of information and communication technology (ICT) on learning achievement, analyzed qualitatively, describing the data in the form of sample size, st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…Therefore, the students could smoothly follow the online teaching activities for academic purposes. It is similar to the results of research conducted by Arlinwibowo that groups of students who utilize information and communications technology (ICT) in learning have better learning outcomes than those who do not use ICT [18]. As a result, 50% stated that online education could assist them during knowledge and consultation.…”
Section: Introductionsupporting
confidence: 80%
“…Therefore, the students could smoothly follow the online teaching activities for academic purposes. It is similar to the results of research conducted by Arlinwibowo that groups of students who utilize information and communications technology (ICT) in learning have better learning outcomes than those who do not use ICT [18]. As a result, 50% stated that online education could assist them during knowledge and consultation.…”
Section: Introductionsupporting
confidence: 80%
“…During the automatic pandemic, the use of information technology media plays an important role (He et al, 2021). We can learn how the positive effects of using technology in supporting the learning process (Arlinwibowo et al, 2022). The results also show that the use of information media can be a solution for a new educational model Marsigit et al, 2020).…”
Section: Discussionmentioning
confidence: 92%
“…In terms of technical support such as guidelines, technicians, or people that help in case teachers have difficulties while using VLE, the study found that this support is at a moderate level. Teachers need technical support when employing VLE innovations since such assistance encourages teachers to expand their knowledge and skills to integrate technology [35]. User-friendly features (easy to use) possessed by the VLE application also show to be at a moderate level.…”
Section: Discussionmentioning
confidence: 99%